Ecological carrying capacity in mariculture: Consideration and application in geographic strategies and policy. (April 2023) - Fisher, Jeffrey; Angel, Dror; Callier, Myriam; Cheney, Daniel; Filgueira, Ramon; Hudson, Bobbi; McKindsey, Christopher W.; Milke, Lisa; Moore, Heather; O'Beirn, Francis; O'Carroll, Jack; Rabe, Berit; et al.
Abstract: Governance and management strategies for aquaculture development were examined for a select number of jurisdictions covering a range of marine aquaculture production to better understand the degree to which concepts of "Ecological Carrying Capacity" (ECC) are incorporated into management tools or permitting requirements for aquaculture development. Policies, regulations, and strategic plans were sought through professional knowledge and, at times, using web-based searches. Aquaculture ECC, defined here as, "the magnitude of aquaculture production that can be supported without leading to unacceptable changes in ecological process, species, populations, or communities in the environment, " was not strictly applied in any jurisdiction's aquaculture policy documentation. A broadened search to consider the concept of aquaculture carrying capacity (CC) more generally was conducted. Of the ten nations examined, CC concepts could be found in policy documentation of several nations. The inclusion of CC concepts in policy and strategic planning can be used as part of a suite of management tools to promote sustainable aquaculture within FAO's Ecological Approach to Aquaculture.